2023
DOI: 10.3390/jcm12051882
|View full text |Cite
|
Sign up to set email alerts
|

Specific Learning Disabilities and Emotional-Behavioral Difficulties: Phenotypes and Role of the Cognitive Profile

Abstract: Specific Learning Disabilities (SLD) are often associated with emotional-behavioral problems. Many studies highlighted a greater psychopathological risk in SLD, describing both internalizing and externalizing problems. The aims of this study were to investigate the emotional-behavioral phenotype through the Child Behavior Checklist (CBCL), and evaluate the mediating role of background and cognitive characteristics on the relationship between CBCL profile and learning impairment in children and adolescents with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, most of the questionnaires included in this study were specifically symptom-oriented (e.g., THI for patients with tinnitus, GÜF for patients with hyperacusis); thus, the relevance of these questionnaires for healthy patients is unclear. In addition, the design of the UNITI-RCT, including audiological assessments and multiple questionnaires, prevented the use of other relevant tests for the detection of cognitive impairment, such as the Weschler intelligence test [ 48 ], Mini-Mental State Examination [ 49 , 50 ], or the Beck Depression Inventory-II [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the questionnaires included in this study were specifically symptom-oriented (e.g., THI for patients with tinnitus, GÜF for patients with hyperacusis); thus, the relevance of these questionnaires for healthy patients is unclear. In addition, the design of the UNITI-RCT, including audiological assessments and multiple questionnaires, prevented the use of other relevant tests for the detection of cognitive impairment, such as the Weschler intelligence test [ 48 ], Mini-Mental State Examination [ 49 , 50 ], or the Beck Depression Inventory-II [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This questionnaire has 25 and 3 subscales: functional, emotional and catastrophizing tinnitus. Total scores range from 0 to 100 points, with 5 levels of severity: very mild (0-16), mild (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), moderate (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56), severe (58-76), and catastrophic (78-100) [18,[22][23][24].…”
Section: Tinnitus Handicap Inventorymentioning
confidence: 99%
“…Furthermore, it is known from the literature [17][18][19] that university students with SLD show great psychological suffering related to their leaning difficulties that may affect self-esteem and motivation and may be accompanied by emotional and social difficulties. Recently, a study conducted on Italian students with SLD found a mediating role of cognitive characteristics on the relationship between emotional-behavioral profile and learning impairment [65]. According to D'Elia and colleagues [54], taking into account the specific cognitive profiles of these students also means ensuring a greater understanding of the resources to be enhanced to support not only their cognitive growth, but also their emotional and social well-being.…”
Section: Discussionmentioning
confidence: 99%
“…With average intellect and reasonable educational and socio-cultural chances, specific learning disabilities (SLDs), and neuro-developmental disorders, are defined by difficulties with reading, writing, and math skills. SLDs happen without mental, sensory, or neurological problems (Cristofani et al 2023). Emotional-behavioural Disorders (EBD) are provided to an estimated 353,000 students in the US (Gersib and Mason 2023).…”
Section: Introductionmentioning
confidence: 99%